Fenomena Phubbing: Peran Teknologi Komunikasi Dalam Perubahan Interaksi Sosial - Sitorus, Hema Junaice; ., Irwansyah (CV. ITTC INDONESIA, 2024)
The rapid advances in communication technology have an impact on our daily lives, careers, and modes of communication. IoT (Internet of Things), e-learning, AI (Artificial Intelligence), cloud computing, mobile apps, virtual reality (VR), and augmented reality (AR) communication are some of the key aspects in the development of communication technology. These trends explain how advancements in communication technology could impact daily interactions and lifestyle choices. Even while these developments create opportunities for efficiency and connectivity, it's essential to understand and deal with the societal problems and consequences that these developments also bring with it. Phubbing has become a thing as a consequence of technology use gone wrong.